Repetitions of Desire: Queering the One Direction Fangirl. Issue 1 (1st March 2019) - McCann, Hannah; Southerton, Clare
Abstract : Like other fangirls, fans of former boyband One Direction ("Directioners") have often been represented in media discourse as obsessive and hysterical, with fan behaviour interpreted as longing for heterosexual intimacy with band members. Subverting this heteronormative framing, a group of Directioners known as "Larries" have built a sub-fandom around imagining a relationship ("ship") between two of the band members, Harry Styles and Louis Tomlinson. Representation of the Larry fandom has gone beyond pathologizing fangirls to framing their shipping practice in terms of "fake news." The conspiracy theory panic around Larries misses the complex ways that subtext and queer reading are mobilized within the fandom to invoke feelings of queer intimacy and belonging. Drawing on a digital ethnography conducted on Twitter with Larries, we argue that these fans engage in queer reading strategies to explicitly imagine and interrupt dominant heterosexual narratives, and thus queer the figure of the fangirl.